1995
DOI: 10.1093/oxfordjournals.aje.a117743
|View full text |Cite
|
Sign up to set email alerts
|

Retinol, Antioxidant Vitamins, and Cancers of the Upper Digestive Tract in a Prospective Cohort Study of Postmenopausal Women

Abstract: Very few prospective studies have reported previously on the association of micronutrient intake and the risk of cancers of the upper digestive tract (mouth, pharynx, esophagus, and stomach) in western populations. During 7 years of follow-up in the Iowa Women's Health Study, from 1986-1992, 59 of the 34,691 at-risk cohort members developed cancers of the upper digestive tract. The association of retinol and antioxidant vitamins (carotene and vitamins C and E) were evaluated separately for cancers of the mouth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
74
2
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 0 publications
1
74
2
2
Order By: Relevance
“…Despite this potential, results from previous reports on dietary intake of carotenoids assessed from dietary questionnaires have been mixed and many have not shown strong associations with GC risk (Chyou et al, 1990;Zheng et al, 1995;Botterweck et al, 2000b). To date, only a few studies have considered prediagnostic blood levels of carotenoids in association with GC risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this potential, results from previous reports on dietary intake of carotenoids assessed from dietary questionnaires have been mixed and many have not shown strong associations with GC risk (Chyou et al, 1990;Zheng et al, 1995;Botterweck et al, 2000b). To date, only a few studies have considered prediagnostic blood levels of carotenoids in association with GC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several case -control studies have shown strong inverse associations between GC risk and higher consumption of some of these nutrients (Buiatti et al, 1990(Buiatti et al, , 1991Gonzalez et al, 1994;Hansson et al, 1994;Ekstrom et al, 2000). Results from prospective dietary studies are conflicting and show either a strong protection (Zheng et al, 1995) or no clear inverse associations between the dietary intake of carotenoids and GC risk (Ocke et al, 1995;Botterweck et al, 2000b).…”
mentioning
confidence: 99%
“…Clarification of the protective mechanisms of fruits, vegetables and whole grains is important to our understanding of cancers of the upper aerodigestive tract. In an analysis of the Iowa Women's Health Study (IWHS), a prospective cohort study of initially 55-to 69-year old women living in Iowa, Zheng et al 13 reported lower dietary intake of yellow/orange vegetables and of carotene, vitamins C and E and retinol in the 59 women who developed upper digestive tract cancers between 1986 and 1992.Our primary focus was to study whether, after 14 years of follow-up in the IWHS, whole-grain intake is related to reduced risk of upper aerodigestive tract cancers. At the same time, we reviewed evidence for the established lifestyle risk factors: low fruit and vegetable intake, smoking and alcohol intake.…”
mentioning
confidence: 99%
“…Clarification of the protective mechanisms of fruits, vegetables and whole grains is important to our understanding of cancers of the upper aerodigestive tract. In an analysis of the Iowa Women's Health Study (IWHS), a prospective cohort study of initially 55-to 69-year old women living in Iowa, Zheng et al 13 reported lower dietary intake of yellow/orange vegetables and of carotene, vitamins C and E and retinol in the 59 women who developed upper digestive tract cancers between 1986 and 1992.…”
mentioning
confidence: 99%
“…The association between other components of fruit and vegetables (e.g., folate, dietary fiber, and carotenoids) 19 -22 and the use of vitamin-containing supplements 11,21 and the risk of gastric carcinoma have been investigated only in a few studies.…”
mentioning
confidence: 99%